2019
DOI: 10.1111/ner.12787
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Emotional Experience Using Electrical Stimulation of the Medial-Prefrontal Cortex: A Preliminary tDCS-fMRI Study

Abstract: Results of this study indicate the potential capacity of tDCS to facilitate brain activation in mPFC regions underlying implicit regulation of emotion and accordingly modulate subjective emotional experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 96 publications
1
35
0
Order By: Relevance
“…Comparable effects were found during the processing of happy compared to fearful faces [15]. In addition, several studies from other groups point to a more general modulation capability of vmPFC by tDCS that is not limited to the mere viewing of emotional stimuli [16][17][18][19][20]. All these studies investigated effects of a single tDCS session.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable effects were found during the processing of happy compared to fearful faces [15]. In addition, several studies from other groups point to a more general modulation capability of vmPFC by tDCS that is not limited to the mere viewing of emotional stimuli [16][17][18][19][20]. All these studies investigated effects of a single tDCS session.…”
Section: Introductionmentioning
confidence: 99%
“…The present study has several strengths. First, to our knowledge only a few studies focus on increasing empathic abilities [62][63][64][65][66][67][68] or modulate externalizing behavior [69][70][71][72], but none of the studies focus on the implication of tDCS in a forensic sample. These individuals are in need of effective care, and by modulating the brain activity this can be a first step towards a new treatment program.…”
Section: Discussionmentioning
confidence: 99%
“…Although there seems to be a clear association between empathy and vmPFC function, only a few studies have investigated modulation of the vmPFC. Abend and colleagues [68] show in their study combining tDCS and fMRI that stimulating with tDCS demonstrated increased emotion-related activation in the vmPFC. Two studies show that anodal stimulation of the (right) vmPFC increases empathic ability and morality [67,68].…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on past research (Mulder et al, 1994; Ward et al, 2018; Quilty et al, 2017; Seon-Young et al, 2007), we investigated the possibility of predicting rTMS response using temperament and character inventory (TCI) trait parameters. We also expected temporary coupling changes in the sgACC to correspond to differences in self-rated emotional state (Abend et al, 2018; Drevets et al, 2008; Nitsche et al, 2012; Mondino et al, 2015: Leyman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%